REVIEW ON MAJOR DEPRESSIVE DISORDER AND COGNITIVE BEHAVIORAL THERAPY - ÖZÇİLOĞLU, Fulya; KARAAZİZ, Meryem (SSD Journal, 2025)
The aim of this review is to examine the effectiveness of Cognitive Behavioral Therapy in people with Major Depressive Disorder. This study used a systematic review method and did not include a field study or any measurement tool. These studies were reviewed in Turkish and English between 2013 and 2024. This review study was divided into two stages, planned to be completed in February 2025 and May 2025. As a result of the literature review, 10 studies were analyzed. In these 10 studies, it was seen that Cognitive Behavioral Therapy is a very effective treatment method in terms of being educational in the treatment of Major Depressive Disorder and achieving effective results in a short time. It was observed that the symptoms were significantly reduced and in some cases completely eliminated after the Cognitive Behavioral Therapy model was applied to people diagnosed with Major Depressive Disorder. Therefore, the Cognitive Behavioral Therapy model is an extremely effective treatment method in the treatment of Major Depressive Disorder.